Real life hexavalent vaccination among children as a practical guide for public health professionals: Four years (from 2016 to 2019) of clinical practice in Sicily, Italy. Issue 6 (30th November 2022) - Costantino, Claudio; Cimino, Livia; Bonaccorso, Nicole; Conforto, Arianna; Sciortino, Martina; Blangiardi, Francesco; Bosco, Girolama; Canzoneri, Gaspare; Casuccio, Nicolò; Collura, Calogero; Cuccia, Mario; Furnari, Roberto; et al.
ABSTRACT: Hexavalent (HV) vaccination is a priority for newborn protection and in Italy is included in the National Immunization Plan with a three doses cycle at 61, 121 and 301 days of age. A retrospective clinical study has been conducted to evaluate real life clinical practice of HV vaccination in the fourth most populous Italian Region. Data on the completion of the HV cycle, on the interchangeability between the two HV adopted in 2016–2017 (DTaP3-IPV-HB/Hib) and 2018–2019 (DTaP5-IPV-HB-Hib) and on the use above the established age, were collected in five Sicilian Local Health Authorities. Data showed an average 91.5% completion of the vaccination cycle at 24 months of age. The average age of administration was significantly higher in children who switched between the two hexavalent vaccines compared to those who completed the vaccination cycle with the same product ( p -value <.01). Interchangeability with one or two doses of HV was also documented in 17.8% (2018) and 16% (2019) of vaccinated infants. Co-administration with other vaccines included in the Sicilian Vaccination Schedule was 85% with anti-pneumococcal vaccination and 65% with anti-rotavirus vaccination. Children vaccinated above recommended age (from 15 to >36 months) significantly after the introduction of mandatory vaccination in Italy ( p -value <.001). This retrospective analysis will contribute to manage potential disruptions due to missed routine immunization opportunities, as the pandemic has caused, with strategies such as catch up above recommended age as well as interchangeability. Data could also help to demonstrate the need to optimize vaccine sessions through co-administration, that strongly contribute to increase vaccination coverage rates and respect of timing of vaccination schedules.